Deletion of the Clostridium thermocellum recA gene reveals that it is required for thermophilic plasmid replication but not plasmid integration at homologous DNA sequences. (1st August 2018) - Groom, Joseph; Chung, Daehwan; Kim, Sun-Ki; Guss, Adam; Westpheling, Janet
Abstract: A limitation to the engineering of cellulolytic thermophiles is the availability of functional, thermostable (≥ 60 °C) replicating plasmid vectors for rapid expression and testing of genes that provide improved or novel fuel molecule production pathways. A series of plasmid vectors for genetic manipulation of the cellulolytic thermophile Caldicellulosiruptor bescii has recently been extended to Clostridium thermocellum, another cellulolytic thermophile that very efficiently solubilizes plant biomass and produces ethanol. While the C. bescii pBAS2 replicon on these plasmids is thermostable, the use of homologous promoters, signal sequences and genes led to undesired integration into the bacterial chromosome, a result also observed with less thermostable replicating vectors. In an attempt to overcome undesired plasmid integration in C. thermocellum, a deletion of recA was constructed. As expected, C. thermocellum ∆recA showed impaired growth in chemically defined medium and an increased susceptibility to UV damage. Interestingly, we also found that recA is required for replication of the C. bescii thermophilic plasmid pBAS2 in C. thermocellum, but it is not required for replication of plasmid pNW33N. In addition, the C. thermocellum recA mutant retained the ability to integrate homologous DNA into the C. thermocellum chromosome. These data indicate that recA can be required for replication of certain plasmids, and that a recA -independent mechanism exists for the integration of homologous DNA into the C. thermocellum chromosome. Understanding thermophilic plasmid replication is not only important for engineering of these cellulolytic thermophiles, but also for developing genetic systems in similar new potentially useful non-model organisms.